ANALISIS BAHAN AJAR DIGITAL BERASIS HEYZINE FLIPBOOK TERHADAP KETERAMPILAN BERPIKIR KRITIS PEMBELAJARAN IPAS DI SEKOLAH DASAR - Dian Fitri; Oktaviani Adhi Suciptaningsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Hyzine flipbook-based digital teaching materials in IPAS (Natural and Social Sciences) learning at primary school level can help students in learning activities. This study aims to explore the impact of using these digital teaching materials on students' critical thinking skills. The research method used is a descriptive quantitative method based on the philosophy of postpositivism used to research on natural object conditions (where the researcher is the key instrument). Data collection techniques are triangulated (combined), data analysis is inductive / qualitative, and the results of this study emphasize meaning rather than generalisation. The data sources in this study came from interviews and questionnaires with several fifth grade students and class teachers, direct observation or observation in the classroom, as well as documentation such as photos, and digital teaching materials in the form of hyzine flipbook. Then the data and questionnaires obtained were analysed with interactive analysis techniques that have been announced by Miles and Huberman. pretest-posttest control group design. The research subjects consisted of two groups, namely the experimental group using flipbook-based digital teaching materials and the control group using conventional teaching materials. Data collection was done through tests and observations. Then the data and questionnaires obtained were analysed using the interactive analysis technique described by Miles and Huberman. The findings show that flipbook-based digital teaching materials can be an effective alternative in improving IPAS learning at the primary school level. The implication of this study is the importance of technology integration in the development of teaching materials to improve the quality of learning in the digital era.